Intervention in OSH for SMEs Employers: Influence in Knowledge and Prevention Activities - Lopes, André M. (2021)
Small and Medium-sized Enterprises (SMEs) face several difficulties compared to large enterprises, such as the lack of human, economic and technological resources. This could lead to difficulties in identifying, assessing and controlling occupational risks and, as a consequence, in having a good Occupational Safety and Health (OSH) performance. Employers of SMEs are responsible for the most part of decision making, namely in OSH. OSH interventions are important to change the behaviors and attitudes to the target group and may encourage both employers and employees to be more active and conscious about OSH in their enterprises. This study aims to design and implement a training session that target employers of micro and small-sized enterprises and analyze its effect on employers’ OSH knowledge and on the preventions activities carried out. The training session was divided in two parts, the first was more theorical and the second more practical. A questionnaire was developed and applied to assess the intervention effect. One month after the intervention, most of participants increased their participation in OSH activities, but were reluctant to invest financial resources to implement measures that promote OSH. The effect of the intervention in employers’ knowledge was limited. This study contribute to the design future OSH interventions in SMEs, suggesting important topics to address and provide information about how to assess its effectiveness.